Thermal and mechanical properties of poly(arylene ether ketone)s having pendant tertiary butyl groups - Yildiz, Emel; Inan, Tuelay Yilmaz; Yildirim, Hueseyin; Kuyulu, Abduelkadir; Guengoer, Atilla (SPRINGER, 2007)
An aromatic bisphenol which contains bulky tertiary butyl group, 5-tert-butyl-1,3-bis(4-hydroxybenzoyl)benzene (2) was synthesized in high yield and purity by the reaction of 5-tert-butyl-1,3-bis(4-fluorobenzoyl)benzene with KOH solution in presence of DMSO. It was polymerized with activated bisarylhalides via aromatic nucleophilic substitution reaction to prepare a series of high molecular weight poly(arylene ether ketone)s (P1-P5), containing pendant tertiary butyl groups. The effect of molecular structure on the physical, thermal, mechanical and adhesion properties of the polymers were investigated.
Keywords: high performance polymers; mechanical properties; polycondensation; poly(arylene ether ketones); BIS(ARYL CHLORIDE)S; SUBSTITUTION; Polymer Science